HUBUNGAN ANTARA DEMOKRASI PARTAI POLITIK DALAM PEMILIHAN UMUM DI INDONESIA: (Dalam Tinjauan Sosiologi Politik) - Athiyyatul Mufidah; Abdullah Syarofi (The Republic : Journal of Constitutional Law, 2024)
Democracy is a form of government in which all citizens have equal rights to make decisions that can change their lives. Democracy allows citizens to participate either directly or through representatives in the formulation, development and creation of laws. The process of establishing democracy is a process of institutionalizing uncertainty, placing all interests in uncertainty. Political parties are autonomous groups of citizens, have the function of making nominations and participating in elections, have the desire to guide control over government power and continue to seize public positions within the organization. government. The main function of political parties is to seek and defend power to realize programs prepared based on ideology certain. The most substantial understanding of democracy is general elections. General elections are an opportunity for citizens to vote officials in government and decide what they want to be carried out by the government. When elections are used as a manifestation of the principle of popular sovereignty, from then on the people are given the freedom to determine candidates for people's representatives who are members of political parties. The will of the people is the basis of government power. This will will be born in periodic and honest elections carried out in general and equal elections. Thus, freedom, honesty, confidentiality and equality are essential things in holding elections.